The role of HIV/AIDS committees in effective workplace governance of HIV/AIDS in South African small and medium-sized enterprises (SMEs) - Jocelyn R Vass (Taylor & Francis Group, 2008)
The primary purpose of this study was to assess the role, status and scope of workplace HIV/AIDS committees as a means of effective workplace governance of the HIV/AIDS impact, and their role in extending social protective HIV/AIDS-related rights to employees. In-depth qualitative case studies were conducted in five South African small and medium-sized enterprises (SMEs) that were actively implementing HIV/AIDS policies and programmes. Companies commonly implemented HIV/AIDS policies and programmes through a workplace committee dedicated to HIV/AIDS or a generic committee dealing with issues other than HIV/ AIDS. Management, through the human resources department and the occupational health practitioner often drove initial policy formulation, and had virtually sole control of the HIV/AIDS budget. Employee members of committees were mostly volunteers, and were often production or blue collar employees, while there was a notable lack of participation by white-collar employees, line management and trade unions. While the powers of workplace committees were largely consultative, employee committee members often managed in an indirect manner to secure and extend social protective rights on HIV/AIDS to employees, and monitor their effective implementation in practice. In the interim, workplace committees represented one of the best means to facilitate more effective workplace HIV/AIDS governance. However, the increased demands on collective bargaining as a result of an anticipated rises in AIDS-related morbidity and mortality might prove to be beyond the scope of such voluntary committees in the longer term.